2020
DOI: 10.1080/09168451.2020.1740971
|View full text |Cite
|
Sign up to set email alerts
|

Vascular plant one-zinc finger 1 (VOZ1) and VOZ2 negatively regulate phytochrome B-mediated seed germination inArabidopsis

Abstract: Seed germination is regulated by light. Phytochromes (Phys) act as red and far-red light photoreceptors to mediate seed germination. However, the mechanism of this process is not well understood. In this study, we found that the Arabidopsis thaliana mutants vascular plant one-zinc finger 1 (voz1) and voz2 showed higher seed germination percentage than wild type when PhyB was inactivated by far-red light. In wild type, VOZ1 and VOZ2 expression were downregulated after seed imbibition, repressed by PhyB, and upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…The expression level of both VOZ genes is downregulated during imbibition in the light; in addition, in pif mutant seeds, expression of VOZ genes was reduced irrespective of light conditions, indicating that VOZ1 and VOZ2 act downstream PIF1 which induces their expression in the dark [23]. By means of a ChIP assay, it was proved that VOZ2 directly binds the GA3ox1 promoter to repress its expression, consistent with increased expression level of the GA3ox1 gene in voz1voz2 double mutant seeds [23]. Interestingly, this scenario is very reminiscent of the one previously shown for the DAG1 protein, which is induced indirectly by PIF1 and in turn represses GA3ox1 expression to inhibit phyB-dependent seed germination [17,24].…”
Section: Light and Phytohormones Crosstalk From Seed Dormancy And Germentioning
confidence: 99%
See 2 more Smart Citations
“…The expression level of both VOZ genes is downregulated during imbibition in the light; in addition, in pif mutant seeds, expression of VOZ genes was reduced irrespective of light conditions, indicating that VOZ1 and VOZ2 act downstream PIF1 which induces their expression in the dark [23]. By means of a ChIP assay, it was proved that VOZ2 directly binds the GA3ox1 promoter to repress its expression, consistent with increased expression level of the GA3ox1 gene in voz1voz2 double mutant seeds [23]. Interestingly, this scenario is very reminiscent of the one previously shown for the DAG1 protein, which is induced indirectly by PIF1 and in turn represses GA3ox1 expression to inhibit phyB-dependent seed germination [17,24].…”
Section: Light and Phytohormones Crosstalk From Seed Dormancy And Germentioning
confidence: 99%
“…The VASCULAR PLANT ONE-ZINC FINGER 1 and 2 (VOZ1 and VOZ2) were recently added as downstream elements of the phyB-PIF1 signaling pathway; VOZ1 and VOZ2 transcription factors have been previously characterised as phyB-interacting proteins which redundantly promote flowering [22]. Interestingly, it has been demonstrated that voz1voz2 double mutant seeds -conversely to the single voz1 and voz2 mutants -show a higher germination rate than the wild type under phyB-off conditions, (after a pulse of far red light), suggesting that the VOZ proteins redundantly repress phyB-mediated seed germination [23]. The expression level of both VOZ genes is downregulated during imbibition in the light; in addition, in pif mutant seeds, expression of VOZ genes was reduced irrespective of light conditions, indicating that VOZ1 and VOZ2 act downstream PIF1 which induces their expression in the dark [23].…”
Section: Light and Phytohormones Crosstalk From Seed Dormancy And Germentioning
confidence: 99%
See 1 more Smart Citation
“…The VASCULAR PLANT ONE-ZINC FINGER 1 and 2 (VOZ1 and VOZ2) were recently added as downstream elements of the phyB-PIF1 signaling pathway; VOZ1 and VOZ2 transcription factors have been previously characterized as phyB-interacting proteins which redundantly promote flowering [23]. Interestingly, it has been demonstrated that voz1voz2 double mutant seeds-conversely to the single voz1 and voz2 mutants-show a higher germination rate than the wild type under phyB-off conditions, (after a pulse of far red light), suggesting that the VOZ proteins redundantly repress phyB-mediated seed germination [24]. The expression level of both VOZ genes is downregulated during imbibition in the light; in addition, in pif mutant seeds, expression of VOZ genes was reduced irrespective of light conditions, indicating that VOZ1 and VOZ2 act downstream PIF1 which induces their expression in the dark [24].…”
Section: Light Control Of Seed Dormancy and Germinationmentioning
confidence: 99%
“…Interestingly, it has been demonstrated that voz1voz2 double mutant seeds-conversely to the single voz1 and voz2 mutants-show a higher germination rate than the wild type under phyB-off conditions, (after a pulse of far red light), suggesting that the VOZ proteins redundantly repress phyB-mediated seed germination [24]. The expression level of both VOZ genes is downregulated during imbibition in the light; in addition, in pif mutant seeds, expression of VOZ genes was reduced irrespective of light conditions, indicating that VOZ1 and VOZ2 act downstream PIF1 which induces their expression in the dark [24]. By means of a ChIP assay, it was proved that VOZ2 directly binds the GA3ox1 promoter to repress its expression, consistent with increased expression level of the GA3ox1 gene in voz1voz2 double mutant seeds [24].…”
Section: Light Control Of Seed Dormancy and Germinationmentioning
confidence: 99%